Effect of Drip Fertigation on Yield, Water Use Efficiency, and Nutrients Availability in Banana in West Bengal, India. Issue 13 (5th August 2016) - Pramanik, Sanjit; Lai, Sonamuni; Ray, R.; Patra, S. K.
ABSTRACT: Field studies were conducted during 2008–2009 and 2009–2010 at the Gangetic alluvial plains of West Bengal, India, to assess the different levels of drip fertigation at variable evaporation replenishment compared to surface irrigation and conventional soil fertilization on yield, water use efficiency, and nutrients availability in plant and ratoon crop of banana. The experiment was laid in an Augmented Factorial Complete Block Design with three replications having three drip irrigation schedules at 50%, 60%, and 70% of cumulative pan evaporation (CPE) and three drip fertigation schedules at 50%, 60%, and 80% of recommended nitrogen, phosphorus, and potassium (NPK) fertilizers with inclusion of conventional surface irrigation at 100% of IW/CPE. The results showed that fruit yield of plant and ratoon crop increased progressively with increasing levels of irrigation water (up to 60% CPE) and NPK fertigation through the drip system. However, maximum fruit yield and water use efficiency of crops was obtained with drip irrigation at 60% CPE with NPK fertigation at 80% of recommended dose. Drip irrigation, as a whole, registered higher fruit yields and water use efficiency with savings of 38.3–41.5% of water compared to surface irrigation. Availability of N, P, and K in soil at vegetative, shooting, and harvesting stages for plant and ratoon crop consistently increased with increasing rate of irrigation water and NPK fertigation through the drip system. Higher availability of macronutrients in soil was recorded with drip irrigation at 70% CPE with 80% of recommended drip NPK fertigation. Overall drip fertigation system improved the available plant nutrients in the soil as compared with traditional surface irrigation.